Demo of Bayesian linear models - Henriksson, Johan (SciLifeLab Serve, 2026)
Demo of Bayesian linear models for teaching purposes. By Johan Henriksson, www.henlab.org. Source at https://github.com/henriksson-lab/demo_bayesianlinmod